Bridge Construction Impacts the Adjacent Channel Morphology and Turbidity: A Study on a Dying Distributary of River Padma - Balai Chandra Das; Aznarul Islam; Shrabani Das; Riya Adhikary; Rohini Sarkar (Earth Science, Systems and Society)
River-road crossings are one of the basic infrastructures for rolling the wheels of development of the modern world facilitating connectivity and overcoming geographical obstacles. Their impacts on the hydro-geomorphology of the riverine landscape and the lotic habitat is a long concerning issue amongst scientists, planners and stakeholders. The construction of a new highway bridge over the Jalangi River commenced a few years ago, experiencing occasional halts and progressing at a notably sluggish pace. However, in 2022, the construction gained momentum and was completed in 2023. The study aims to evaluate the influence of the bridge and its construction procedures on the river’s channel morphology and turbidity. We gathered data on various structural aspects of the recently built highway bridge at Krishnagar spanning the Jalangi River, a dying distributary of the Padma River. This included assessments of channel geomorphology and information to water turbidity. To assess the impact of road crossing on channel geomorphology we applied tools of w/d ratio, channel efficiency and channel asymmetry (A*). At-a-station channel geomorphology of the river was drastically impacted by the structure of the bridge and its construction processes. As the river is a dying one, the impulse of road crossing felt to the downstream insignificant. The impact of road-river crossing on water turbidity appears significant at the construction site. Non-clearance of debris and soil from river beds and banks obstructed animal movement along the river banks. In like environments where robust data forms the foundation, it is recommended to pursue additional research to identify a mitigation strategy for the way forward.